Efforts to Improve Early Reading Skills and Learning Motivation Through Digital Flipbook Media - Aisyah, Rona All; Wibowo, Setiawan Edi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This study aims to describe: 1) the implementation of the digital flipbook “Children’s Story Collection” to improve students' early reading skills; 2) the implementation of the digital flipbook “Children’s Story Collection” to enhance students' learning motivation; and 3) the improvement of early reading skills and learning motivation of First-grade students at Karangnongko Klaten 1 Elementary School through the use of the digital flipbook “Children’s Story Collection”. The research design employed was classroom action research, which involves planning, implementation, observation, and reflection. The research subjects were 18 first-grade students at Karangnongko Klaten 1 Elementary School. Data collection techniques included tests, observations, interviews, and documentation. Data were analysed using both quantitative and qualitative methods. The results show that: (1) the use of digital flipbook “Children’s Story Collection” can improve early reading skills, as students find it easier to read word by word. The teacher acts more as a motivator and facilitator, while the learning process becomes student-centered; and (2) the use of digital flipbook “Children’s Story Collection” increases students' learning motivation, creating a pleasant and conducive classroom atmosphere. In conclusion, the use of digital flipbook media can improve early reading skills and enhance students' learning motivation. This study implies that teachers can effectively utilise digital flipbook media as a learning tool.